(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Due to the rise of web-based content publishing services, there is an urgent need for adaptive, secure, and scalable solutions for managing blogs. Platforms like WordPress and Ghost are characterized by several limitations, such as inflexibility, insufficient security measures, and scalability issues. In this paper, a Blog Management System (BMS) was implemented using the Django 4.2 framework and Python 3.11 programming language. It includes role-based access control (RBAC), RESTful web APIs through Django REST Framework, full-text search enabled by the PostgreSQL tsvector module with the help of the GIN index, automated spam filtering utilizing Akismet, and asynchronous task management via Celery. A multi-tiered security model according to the OWASP Top-10 list was implemented across seven layers. The performance analysis performed by Locust v2.18 (with 100 concurrent users) showed that the P95 latency did not exceed 200 ms and that the application benefited from an 18× performance gain due to Redis caching. The usability test with 30 users resulted in a SUS score of 83.4 (Grade B+, Excellent), whereas the baseline for WordPress was 72.1.